Desempenho operacional e energético de um trator 4 x 2 TDA no preparo do solo em ambiente semiárido em função da carga dinâmica, pneus e superfície de rolamento - Lopes, José Evanaldo Lima (2018)
The introduction of agricultural tractors in Brazilian agriculture enabled farmers to expand their planting areas, due to the great versatility of these agricultural machines in the accomplishment of numerous operations, indispensable for the implantation and conduction of crops. In view of the changes that occurred in agriculture, it was necessary to carry out studies that point to the improved operational and energy performance of agricultural tractors in mechanized operations. Field trials using data acquisition systems allow for the collection and analysis of information, thus enabling important tools in decision making. The objective of the present work was to evaluate the operational and energy performance of a 4 x 2 - TDA agricultural tractor, as a function of the height of the tire claws, ballasting and rolling surface, performing a soil preparation operation with a scarifier. The experiment was developed at the Curu Valley Experimental Farm (FEVC) belonging to the Federal University of Ceará - UFC, located in the municipality of Pentecoste - Ceará. The experimental design was a randomized block design, with a 2 x 2 x 2 factorial arrangement with four replicates for each treatment, two tire claw heights, two ballasting and two rolling surfaces. For statistical analysis of the data, descriptive statistics and analysis of variance were used. The parameters symmetry and kurtosis were used to perform the normality test of the data. Proceeding to normality was performed the analysis of variance for the means that are normal. The data were submitted to the F-Test using Sisvar 5.6® software and, when necessary, Tukey's test (p<0.10) was applied to compare the averages. It is concluded that: The scarification process contributes to the reduction of soil resistance to penetration in the layers 0.15 - 0.30 and 0.30 - 0.45 m, providing a significant increase in soil water content in layer 0.30 - 0.45 m. Lower skating of the front wheels of the tractor was registered for worn tire, for the rear wheels larger skidding was found for new tire. Working with a worn tire, it was observed a greater speed of displacement and greater effective and operative field capacity of the tractor-scarifier assembly. The worn tires and the ground surface with straw provided less requirement of traction and power in the bar and higher coefficient of traction was found working with worn tires. The hourly fuel consumption was not significantly affected by the treatments analyzed, lower specific fuel consumption was found for mobilized soil and higher fuel consumption per area was observed for new tires. No ballast and mobilized soil provided a larger mobilized area, greater area of elevation of the soil profile was observed working with new tire, the elevation area did not suffer significant alteration by the treatments and greater soil specific resistance was observed in the mobilized soil surface.